Translation of HTLV (human T-cell leukemia virus) RNA in a nuclease-treated rabbit reticulocyte system. - Kobayashi, N (1984)
A human type-C retrovirus, designated HTLV (human T-cell leukemia virus), was isolated from the HTLV producer cell line MT-2. Agarose gel electrophoresis analysis 32P-labeled HTLVMT-2 virion RNA revealed that HTLVMT-2 virion RNA consists mainly of 24S and small amounts of 35S and 32S RNAs. The 24S HTLVMT-2 virion RNA and unfractionated HTLVMT-2 virion RNA were translated in a rabbit reticulocyte lysate system in vitro. The predominant polypeptide synthesized from 24S RNA had an apparent mol. wt. of 28 000 (28 K); unfractionated HTLVMT-2 virion RNA directed the synthesis of 53 000 (53 K), 33 000 (33 K) and 28 000 (28 K) polypeptides as main components. Most of the polypeptides synthesised in vitro by translation of HTLVMT-2 virion RNAs possess the same sizes as the proteins formerly designated as ATLA (ATL-associated antigen) in SDS-polyacrylamide gel electrophoresis and immunologically precipitated with sera of ATL patients. Therefore, the antigens termed ATLA, found by the serological study of ATL, are HTLVMT-2 encoded polypeptides.